Comparison of in-game external load metrics among positions and between halves for division i collegiate women's lacrosse athletes - Kilian, J.; Snyman, K.; Miyashita, T. (International Journal of Strength and Conditioning, 2022)
External load has become a common metric for coaches to track the activity profiles of athletes during training and competition. The advent of wearable technology has made external load monitoring accessible for more coaches. The purpose of this study was to compare positional (attack, midfield, and defense) and game (first half to second) external loads. An NCAA Division I women`s lacrosse team was recruited to wear triaxal accelerometers and GPS units during five non-conference games during the 2020 regular season. The external load metrics evaluated for this study included total distance, sprint distance (> 19 km·hr-1), number of power plays (> 3 m·s-2), top speed, and PlayerLoad. Significance was set at p < 0.05. No significant differences among positions were observed for full game measures (p > 0.05). A significant main effect for time was observed for sprint distance (midfield; p < 0.001 ) and power plays (midfield; p < 0.001 and defense; p = 0.004). While no significant differences occurred for activity profiles among positions, high-intensity efforts (sprint distance and power plays) were significantly less in the second half, likely due to fatigue. Coaches and sports scientists can use this information to manage in-game fatigue through tactics such as strategic substitutions and time-outs, thus preserving the intensity of the activity profiles late in the game.